Å gå seg vill i en ordbok: seg og V+seg i tospråklige ordbøker - Griškevičienė, Aurelija; Berg-Olsen, Sturla (Nordiske Studier i Leksikografi, 2018)
In this article we discuss the treatment of the reflexive pronoun seg and constructions containing verbs and seg in bilingual dictionaries with Norwegian as source language. We argue that the structure of the target language must play a key role when the lexicographer decides how to present the source language material. We propose a typology of construc-tions with verbs and seg, which serves as a basis for the treatment of these constructions in the Norwegian-Lithuanian Dictionary.